Caregiver Burden in Caregivers of Children With Special Health Care Needs and Association With Chronic Pain. Issue 5 (1st May 2022) - Camelo Castillo, Wendy; Onasanya, Oluwadamilola; dosReis, Susan; Hogans, Beth; Reeves, Gloria
Abstract : Background/Objectives: Chronic noncancer pain (CNCP) affects millions of individuals in the United States but evidence of its prevalence among caregivers of children with special health care needs is sparse. We sought to estimate the prevalence of CNCP and its association with caregiver burden, in a nationally representative sample. Methods: Retrospective cross-sectional study using pooled Medical Expenditure Panel Survey data for 2010–2015. Within interviewed households, family groups consisting of at least 1 parent and 1 child (0–17 y) were identified. CNCP was identified by one or more International Classification of Diseases, Ninth Revision (ICD-9)-CM codes utilizing previously published approaches. Level of caregiver burden was defined using a validated screener questionnaire identifying children with high burden of care (ie, special health care needs), for example, high or low burden. We estimated prevalence of CNCP as a function of caregiver burden, as well as the association of risk factors with CNCP, including parent sociodemographic features, clinical diagnoses, and family level characteristics. Results: We identified 46, 525 caregivers of whom 3.6% reported experiencing high caregiving burden. The prevalence of CNCP was 25.5% and 14.0% among parents with high compared with low caregiving burden, respectively. Odds of CNCP were higher among parents with high compared to those with lower caregiver burden (odds ratio=1.29, 95% confidence interval=1.06–1.55). Being obese, experiencing disability, and having a mental health diagnosis were associated with higher odds of CNCP. Conclusions: Chronic pain is more common among caregivers with high caregiver burden. Our findings highlight the need to further explore the nature and impact of risk factors on caregiver health and disability.